Optical sensing properties of Au nanoparticle/hydrogel composite microbeads using droplet microfluidics. (12th September 2017) - Li, Huilin; Men, Dandan; Sun, Yiqiang; Zhang, Tao; Hang, Lifeng; Liu, Dilong; Li, Cuncheng; Cai, Weiping; Li, Yue
Abstract: Uniform Au nanoparticle (NP)/poly (acrylamide-co-acrylic acid) [P(AAm-co-AA)] hydrogel microbeads were successfully prepared using droplet microfluidics technology. The microbeads exhibited a good stimuli-responsive behavior to pH value. Particularly in the pH value ranging from pH 2–pH 9, the composite microbead sizes gradually increased along with the increase of pH value. The homogeneous Au NPs, which were encapsulated in the P(AAm-co-AA) hydrogel microbeads, could transform the volume changes of hydrogel into optical signals by a tested single microbead with a microspectrometre system. The glucose was translated into gluconic acid by glucose oxidase. Thus, the Au NP/P(AAm-co-AA) hydrogel microbeads were used for detecting glucose based on pH effects on the composite microbeads. For this, the single Au NP/P(AAm-co-AA) hydrogel microbead could act as a good pH- or glucose-visualizing sensor.